2020
DOI: 10.1097/gox.0000000000003070
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing the Ideal Nipple-Areolar Complex Position for Chest Masculinization Surgery

Abstract: Background: Chest masculinization surgery is increasing in prevalence. However, the ideal location of the nipple-areolar complex (NAC) is unknown. Our purpose was to determine the most aesthetically favorable male NAC position for use in chest masculinization through crowdsourcing. Methods: Using Adobe Photoshop CC 2017, 8 locations for the NAC were created based on previous literature descriptions. Amazon Mechanical Turk was utilized as a crowdsourcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The NAC was then regrafted to its new position on the thorax with the use of the pectoralis muscle, clavicle, and sternum as landmarks. 7 , 16 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…The NAC was then regrafted to its new position on the thorax with the use of the pectoralis muscle, clavicle, and sternum as landmarks. 7 , 16 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…This is an acceptable shortcoming because previous studies that have used MTurk to ascertain aesthetic preferences have demonstrated that MTurk respondents are a diverse representation of the general population, with variations in gender, age, and country of origin in different studies. 8,31,32 Furthermore, although a general sample from MTurk was used to validate our aesthetic rating scale, it has previously been shown that gender, race or ethnicity, and age affect aesthetic preferences. Thus, we envision future studies that aim to validate this scale among specific clinical samples of patients who are seeking or have undergone abdominoplasty and that detailed demographic data could be collected and integrated into analyses of these data.…”
Section: Ementioning
confidence: 99%